Higher Yogurt Consumption Is Associated With Lower Risk of Colorectal Cancer: A Systematic Review and Meta-Analysis of Observational Studies - Sun, Jiangjie; Song, Jiangyan; Yang, Jie; Chen, Le; Wang, Zuochuan; Duan, Meiwen; Yang, Shuhui; Hu, Chengyang; Bi, Qingquan (Frontiers in Nutrition, 2022)
Background Yogurt is known to be nutrient-rich and probiotic content, which gather optimism due to their potential role in preventing and managing cancers. The effect of yogurt consumption on colorectal cancer (CRC) is inconsistent. Objective: This study aims to investigate the association of yogurt consumption with risk of CRC. Methods: Three databases including PubMed, Web of Science and Embase were searched for all relevant studies through July 2021 on the association of yogurt consumption with CRC risk. We pooled the odds ratios (ORs) and their 95% confidence intervals (95% CIs) using a random-effects meta-analysis to assess the association. Results: Finally, 16 studies met the inclusion criteria and were chosen in the meta-analysis. Yogurt consumption was significantly with lower risk of CRC risk in the overall comparison (OR = 0.87, 95% CI: 0.81–0.94) and in the cohort studies (OR = 0.91, 95% CI: 0.86–0.97) and case-control studies (OR = 0.75, 95% CI: 0.65–0.85). With regard to subgroup analyses by study region, cancer type, publication year and sex, yogurt consumption significantly decreased overall colorectal cancer, colon cancer and distal colon cancer risks. In stratified analyses, we observed significantly decreased CRC risk in Europe and Africa and published after 2010 and overall population. Sensitivity analysis indicated the result is stable and there is no publication bias in the meta-analysis. Conclusions: Overall, this study indicated that yogurt intake was related with a decreased risk of CRC.